The Transmission of Control Through Organizational Hierarchy - Olchi, William G. (Academy of Management Journal, 1978)
This paper addresses the problem of control loss in hierarchies. Data on 215 departments (aggregated from 2,363 individual questionnaires) show that behavior control and output control differ sharply in transmission. Behavior control shows almost no interlevel consistency, while output control is transmitted through three levels of hierarchy with relatively little loss. Further analysis suggests that behavior control is determined by local, particularistic conditions and therefore cannot be expected to show high interlevel consistency or transmission.